Examining emergency department inequities: Do they exist?. (6th May 2019) - Curtis, Elana; Paine, Sarah‐Jane; Jiang, Yannan; Jones, Peter; Tomash, Inia; Raumati, Inia; Reid, Papaarangi
Abstract: Objectives: Ethnic inequities in health outcomes have been well documented with Indigenous peoples experiencing a high level of healthcare need, yet low access to, and through, high‐quality healthcare services. Despite Māori having a high ED use, few studies have explored the potential for ethnic inequities in emergency care within New Zealand (NZ). Healthcare delivery within an ED context is characterised by time‐pressured, relatively brief, complex and demanding environments. When clinical decision‐making occurs in this context, provider prejudice, stereotyping and bias are more likely. The examining emergency department inequities (EEDI) research project aims to investigate whether clinically important ethnic inequities between Māori and non‐Māori exist. Methods: EEDI is a retrospective observational study examining ED admissions in NZ between 2006 and 2012 (5 976 126 ED events). EEDI has been designed from a Kaupapa Māori Research position. Results: The primary data source is the existing Shorter Stays in Emergency Department National Research Project (SSED) dataset that will be combined with clinical information extracted from NZ's National Minimum Dataset. The key predictor variable is patient ethnicity with other covariates including: sex, age‐group, area deprivation, mode of presentation, referral method, Australasian Triage Scale and the Multimorbidity Measure (M3 Index) for co‐morbidities. Generalised linear regression models will be used to investigate the associations between pre‐admission variables and the measures of ED care, and to examine the contribution of each measure of ED care on ethnic inequities in mortality. Conclusion: The present study will provide the largest, most comprehensive investigation of ED outcomes by ethnicity to date in NZ.